Comparative bioavailability of betahistine tablet formulations administered in healthy subjects - Val, Ligia; Chen, Lu Shi; Mendes, Gustavo Duarte; Nucci, Gilberte De (Arzneimittelforschung, 2010)
To assess the comparative bioavailability of two formulations (16 mg tablet) of betahistine (CAS 5579-84-0) in healthy volunteers of both sexes.The study was conducted using an open, randomized, two-period crossover design with a 1-week washout interval. Plasma samples were obtained for up to 36 h post dose. Plasma 2-pyridylacetic acid concentrations were analyzed by liquid chromatography coupled with tandem mass spectrometry (LC-MS-MS) with positive ion electrospray ionization using multiple reaction monitoring (MRM). From the 2-pyridylacetic acid plasma concentration vs. time curves, the following pharmacokinetic parameters were obtained for AUClast and Cmax.The limit of quantification was 4 ng/mL for plasma 2-pyridylacetic acid analysis. The geometric mean and 90% confidence interval (CI) of test/reference percent ratios were: 98.94% (92.21% −106.16%) for Cmax( 95.42% (91.74% −99.25%) for AUClast.Since the 90% CI for Cmax and AUCs ratios were all within the 80–125% interval proposed by the US Food and Drug Administration Agency, it was concluded that the test formulation is bioequivalent to the reference for both the rate and the extent of absorption.
Keywords: Betahistine, bioequivalence, pharmacokinetics; CAS 5579-84-0; LC-MS/MS; 2-Pyridylacetic acid